THE IMAGINED INDEPENDENCE OF CANADA’S INTERNET - Hilstob, Kayla (AoIR Selected Papers of Internet Research, 2021)
Internet scholars are uncovering and connecting military, political and cultural histories of early internets across the globe, including in the US, (Abbate 1999), Chile (Medina 2011) and France (Mailland & Driscoll 2016), respectively. All three approaches inform this history, exploring the Canadian context. On the recommendation of US counterparts at NORAD, a top-secret whitepaper recommended Canada develop a distributed communications network (NORAD 1965), which became SAMSON: Strategic Automatic Message Switching Operational Network. SAMSON developed into an internet, though riddled with a series of setbacks beginning almost immediately, until it was disbanded in 1984. (Canadian Armed Forces 1985). This paper investigates Canada’s internet infrastructural technopolitics through Larkin’s framework of questioning how they “emerge out of and store within them forms of desire and fantasy” (2013, 329). Specifically, it asks how the design, equipment, and network protocols of this Canadian internet embodied the imaginary of Canadian independence from 1965 to 1984, drawing on primary sources from the unpublished documents of the Canadian Armed Forces that have since been declassified. The emergence of the early Canadian internet occurred during a political renewal. At a time of pushback against American and British influence, the Canadian military rejected cooperation with the US, and focused on internal threats over Cold War rivalries (Hatt 1984). By design the Canadian internet was a security apparatus, but the technopolitics embedded in the system dictate who is to be secured against whom. This paper asks how this history persists in Canada’s internet infrastructure today.